2001
DOI: 10.1046/j.1365-3059.2001.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of pathogenesis‐related proteins in the cauliflower (Brassica oleracea var. botrytis)–downy mildew (Peronospora parasitica) pathosystem treated with acibenzolar‐S‐methyl

Abstract: Bretagne Biotechnologie Ve  ge  tale, BBV, Penn-ar-prat, F-29250 Saint Pol-de-Le Âon, France Acibenzolar-S-methyl (ASM), a member of the benzothiadiazoles (BTH), was tested on cauliflower (Brassica oleracea var. botrytis) seedlings for its ability to induce resistance against downy mildew (Peronospora parasitica). Seven-dayold seedlings of the susceptible cultivar Billabong, sprayed with solutions containing 0´015 or 0´075 mg a.i. mL 21 ASM and inoculated 1±8 days later with P. parasitica, were assessed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 33 publications
2
33
2
2
Order By: Relevance
“…Both enzymes can hydrolyse cell walls and kill infecting pathogens ( Van-Loon, 1997). Studies on tobacco and cauliflower showed that enhanced disease resistance in these crops is paralleled by increased activities of chitinase and ␤-1,3-glucanase Wendehenne et al, 1998;Ziadi et al, 2001). In the present study, we show that there was a significant increase (P < 0.05) in the activities of chitinase and ␤-1,3-glucanase in peach fruit as a result of BTH-treatment.…”
Section: Discussionsupporting
confidence: 62%
“…Both enzymes can hydrolyse cell walls and kill infecting pathogens ( Van-Loon, 1997). Studies on tobacco and cauliflower showed that enhanced disease resistance in these crops is paralleled by increased activities of chitinase and ␤-1,3-glucanase Wendehenne et al, 1998;Ziadi et al, 2001). In the present study, we show that there was a significant increase (P < 0.05) in the activities of chitinase and ␤-1,3-glucanase in peach fruit as a result of BTH-treatment.…”
Section: Discussionsupporting
confidence: 62%
“…Comparable results were also reported by Sundar et al (2001) as significantly reducing red rot lesion development in sugarcane pretreatment with CGA-245704 at 100 µg mL -1 applied as soil drench to the potted plants, and effectiveness persisted for up to 30 d after the treatment. Persistent resistance for longer periods was also reported by Ziadi et al (2001) against downy mildew of cauliflower. Dann and Deverall (1996) demonstrated in two consecutive years of field trials that applying 2,6-dichloroisonicotinic acid (INA) to 16-to 20-d-old bean seedlings (cv.…”
Section: Figure 2 Mean Comparison Of Percentage Reduction In Ascochymentioning
confidence: 57%
“…There are at least three types of induced resistance: systemic acquired resistance (SAR) developed by localized necrosis resulting in hypersensitive reaction (HSR), wound-induced resistance usually caused by insect feeding, and infection by virulent pathogen or by treatment with certain chemically induced systemic resistance (ISR) that developed due to plant growth colonization promoting rhizobacteria (PGPR). In systemic acquired resistance, an invading pathogen is not needed and various defense pathways are stimulated in the induced plant resulting in the production of diverse defense products, including lignin and pathogenesisrelated proteins, some of which show chitinase or β-1,3-glucanase activity (van Loon, 1997;Neuhaus, 1999), phytoalexins, thionins, and defensins (Kessmann et al, 1994;Sticher et al, 1997;Kombrink and Schmelzer, 2001;Ziadi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Foliar application of HA (25% active HA) consistently enhanced antioxidants such as á-tocopherol, â-carotene, superoxide dismutases, and ascorbic acid concentrations in turf grass species [50]. These antioxidant may play a role in the regulation of plant development, flowering and chilling of disease resistance [51,52]. Amino acids have a chelating effect on micronutrient when applied, that make the absorption and transportation of micronutrients inside the plant is easier due to its effect on cell membrane permeability.…”
Section: Discussionmentioning
confidence: 99%